Influence of Bentonite Nanoparticles on properties of PVP-CMC-Gums Hydrogel Films for biomedical applications - Idris, Samahir Abdalla Sheikh; Yucel, Ozgun (Journal of engineering sciences and information technology, 2022)
Recently, polymers have been widely employed, and the unique features of hydrogels have found several applications, particularly in biomedical applications. In this work, PVP-CMC-Gums hydrogel films were created from a variety of materials using casting and room-temperature drying processes; however, the impacts of adding bentonite clay, SEM, FTIR, XRD, TGA, swelling, melting, contact angle, and a set of experiments were performed to clarify and analyze a variety of physical, mechanical, thermal, and other characterizations. The main results revealed new peaks indicative of the presence of cross-linking, which is a major driver of loading and release properties, suggesting that these films can be used for drug delivery and a variety of other applications. PCXB film has the best properties in color, surface hydrophobicity, solubility, and swelling, while PCGB film has the best results in biodegradability and permeability, and the two films have strong thermal, and mechanical and release properties. Accordingly, the addition of bentonite clay to hydrogel films improves all their properties, making them suitable for diverse biomedical applications such as root canal fillings, tissue engineering, contact lenses, and dressings.